HUBUNGAN PEMBERIAN ASI EKSLUSIF DAN KONDISI LINGKUNGAN RUMAH DENGAN KEJADIAN DIARE PADA BALITA DI WILAYAH KERJA PUSKESMAS PEKURUN KABUPATEN LAMPUNG UTARA - Umi Romayati Keswara; Akbar Cholidin (Universitas Malahayati Lampung, 2020)
ABSTRACT: THE CORRELATION AMONG EXCLUSIVE BREASTFEEDING AND HOUSING ENVIRONMENT TOWARD DIARRHEA INCIDENCE ON TODDLERS AT WORKING AREA OF PEKURUN HEALTH CENTER OF LAMPUNG UTARA REGENCY IN 2019 Introduction: Diarrhea becomes the main cause of mortality and morbidity of under five year babies. Based on the data from 2018 Basic Health Research, the diarrhea incidence increased from 7% in 2013 became 8% in 2018. Specifically in Lampung Utara Regency, the case was 12,084 cases. In the Pekurun Health Center, there were 419 cases in 2017 where the highest incidence happened at Pekurun Village amounting to 90 cases.Objective: This study was to identify the correlation among exclusive breastfeeding and housing environment toward diarrhea incidence on toddlers at working area of Pekurun Health Center of Lampung Utara Regency in 2019.Method: This study was quantitative with analytical design and cross sectional approach. The population of the study consisted of 7 month – 5 year babies amounting to 1,143 babies registered at working area of Pekurun Health Center of Lampung Utara Regency. The proportional random sampling technique resulted 106 respondents. The statistical analysis was through Chi Square.Result: The frequency distribution of respondents consisted of 39 babies (36.8%) suffering diarrhea, 39 babies (36.8%) receiving exclusive breastfeed, and 48 babies (45.3%) living in bad housing environment. There was a correlation between exclusive breastfeeding and diarrhea incidence (p value 0.043). There was a correlation between housing environment and diarrhea incidence on toddlers (p value 0.018).Conclusion: There was a correlation among exclusive breastfeeding and housing environment toward diarrhea incidence on toddlers. The women should exclusively breastfeed their babies to improve babies’ immunity in order to prevent diarrhea infection and should maintain the hygiene of the housing environment.Keywords : diarrhea, exclusive breastfeeding, environemt, toddlers INTISARI: HUBUNGAN PEMBERIAN ASI EKSKLUSIF DAN KONDISI LINGKUNGAN RUMAH DENGAN KEJADIAN DIARE PADA BALITA DI WILAYAH KERJA PUSKESMAS PEKURUN KABUPATEN LAMPUNG UTARA TAHUN 2019 Pendahuluan: Diare menjadi penyebab utama angka kematian dan angka kesakitan di kalangan anak-anak kurang dari 5 tahun. Berdasarkan data Riskesdas (2018), angka kejadian Diare mengalami peningkatan dari 7% pada tahun 2013 menjadi 8% pada tahun 2018. sedangkan untuk Kabupaten Lampung Utara jumlah kasus sebesar 12.084 kasus. Dan di Puskesmas Pekurun kasus diare sepanjang tahun 2017 sebanyak 419 kasus, dengan kasus tertinggi di Desa Pekurun 90 kasus. Tujuan penelitian: Diketahui hubungan pemberian ASI eksklusif dan kondisi lingkungan rumah dengan kejadian diare pada Balita di Wilayah Kerja Puskesmas Pekurun Kabupaten Lampung Utara Tahun 2019.Metode: Jenis penelitian kuantitatif, rancangan analitik, menggunakan pendekatan cross sectional. Populasi adalah semua balita di Wilayah Kerja Puskesmas Pekurun Kabupaten Lampung Utara yaitu 1.143 balita usia 7 bulan – 5 tahun. Sampel 106 responden, dengan teknik Proportional random sampling. Uji statistik yang digunakan adalah uji Chi Square.Hasil: Distribusi frekuensi responden yang mengalami diare yaitu sebanyak 39 (36.8%) balita, mendapatkan ASI eksklusif sebanyak 39 (36.8%), lingkungan rumahnya tidak memenuhi syarat sebanyak 48 (45.3%), Ada hubungan pemberian ASI eksklusif dengan kejadian diare ( p value 0,043), Ada hubungan kondisi lingkungan rumah dengan kejadian diare pada Balita ( p value 0,018).Kesimpulan: Ada hubungan pemberian ASI eksklusif dan kondisi lingkungan rumah dengan kejadian diare pada Balita. Saran kepada ibu dapat memberikan ASI esksklusif pada bayi sebagai upaya untuk meningkatkan kekebalan tubuh bayi sehingga tidak mudah terserang penyakit infeksi seperti diare dan menjaga kebersihan kondisi lingkungan rumah.Kata Kunci : Diare, ASI Eksklusif, Lingkungan, Balita